Environmental Conservation in Hadith: A Thematic Analysis with Maqāṣid al-Sharī'ah Approach - Hawa Hasna Hakimah; Ahmad Musyafiq; Deby Maulina (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2025)
Abstract The increasingly alarming environmental crisis demands a new approach that is not only technical, but also moral and spiritual. Islam as a comprehensive religion has ecological ethical guidelines sourced from the Qur'an and the hadith of the Prophet Muhammad. This research aims to uncover the values of environmental conservation in hadith and interpret it through the views of classical and contemporary hadith scholars. Using a thematic analysis approach and qualitative-descriptive methods, this study examines a number of hadiths related to the prohibition of polluting the environment, the recommendation to plant trees, cleanliness, and human responsibility as a caliph on earth. The results of the analysis show that the hadiths of the Prophet contain ecological principles such as the prevention of damage (dar' al-mafsadah), the preservation of life, cleanliness as worship, and the ecological mandate of humans. The interpretations of scholars such as al-Nawawi, Ibn Hajar, al-Qurṭubī, and Yusuf al-Qaradawi reinforce that environmental ethics in Islam is rooted in maqāṣid al-shari'ah, specifically ḥifẓ al-nafs, ḥifẓ al-māl, and ḥifẓ al-bi'ah. This research contributes to expanding the Islamic ecotheological paradigm and provides a normative basis for the development of environmental policies based on religious values. Keywords: Caliph fi al-arḍ; Ecological hadith; Environmental conservation; Islamic ethics; Maqāṣid al-syarī'ah.